Landscape composition is a stronger determinant than noise and light of avian community structure in an urbanizing county - Sanchez, Karina A.; Benedict, Lauryn; Holt, Emily A. (Frontiers in Ecology and Evolution, 2023)
Urban development has drastically altered ecosystems with dramatic effects on avian diversity and community structure. Most studies investigating this phenomenon are conducted in large and established cities, with fewer conducted in areas of current urbanization. Measuring avian community structure in recently established and growing cities is necessary to understand which species are being affected in a range of urban environments. There is also a critical need to explore multiple measures of urbanization, as different axes of human influence might have varied effects on wildlife. This study investigated the relationship between avian communities and urban noise, light, and landscape composition in Weld County, CO, one of the United States' fastest growing metropolitan areas. We tested the general hypothesis that avian community assemblages would vary with multiple urban characteristics. We measured noise, light, and landscape composition across 16 sites ranging from urban to non-urban and paired these data with avian species census data. We used multivariate analyses to test for covariance of our three measures of urban characteristics, and to examine patterns of species presence and abundances at sites. Results suggest that developed land and water covary with avian community structure across our study sites. Anthropogenic noise and light did not drive avian community patterns as strongly as percent developed land and water. These three urban characteristics did not covary or form a linear urban to non-urban gradient, suggesting that urbanization can have patchy and unpredictable effects, highlighting the value of measuring urban characteristics separately.